If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 260000 = 480000 Reorder the terms: 260000 + 2y = 480000 Solving 260000 + 2y = 480000 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-260000' to each side of the equation. 260000 + -260000 + 2y = 480000 + -260000 Combine like terms: 260000 + -260000 = 0 0 + 2y = 480000 + -260000 2y = 480000 + -260000 Combine like terms: 480000 + -260000 = 220000 2y = 220000 Divide each side by '2'. y = 110000 Simplifying y = 110000
| 2y+14=-6(x-4) | | -8(2+5)+25+32= | | (x/8)^3 | | 2/3-2x/5=1/4 | | 6(r+12)-3r-48-4= | | 4x^2+2x-13=27-25x | | (4x+9)+(-5+3)= | | -7(a-8)+3a-14= | | 5x+6y=31 | | 7x^2+8x-17=55-47x | | 57+5y-12=17y-11-4y | | d^2+13d+56=0 | | 4/9=y-2/9 | | 7/4•3/4 | | -3(w+9)-13+2w= | | 0=x^3+5x^2-84 | | f(n)=3n-5 | | v=3pir^2 | | 29.5/4 | | X+44+73= | | X^2+7x-90=0 | | 3/8/9=3/4/x | | 7/12=x/144 | | 20/25=x/5 | | 6(y-3)+3y-7= | | 3x-8y=-20 | | 5x-5=4x+8 | | 24x+3(-4+2x)=42 | | y=12.5(14)+150 | | 0.03(3x-36)=-0.9(x-1) | | 4x+14=17x-12 | | 5x^(-1/3)=20 |